Impaired synaptic incorporation of AMPA receptors in a mouse model of fragile X syndrome - Chojnacka, Magdalena; Beroun, Anna; Magnowska, Marta; Stawikowska, Aleksandra; Cysewski, Dominik; Milek, Jacek; Dziembowska, Magdalena; Kuzniewska, Bozena (Frontiers in Molecular Neuroscience, 2023)
Fragile X syndrome (FXS) is the most common monogenetic cause of inherited intellectual disability and autism in humans. One of the well-characterized molecular phenotypes of Fmr1 KO mice, a model of FXS, is increased translation of synaptic proteins. Although this upregulation stabilizes in the adulthood, abnormalities during the critical period of plasticity have long-term effects on circuit formation and synaptic properties. Using high-resolution quantitative proteomics of synaptoneurosomes isolated from the adult, developed brains of Fmr1 KO mice, we show differential abundance of proteins regulating postsynaptic receptor activity of glutamatergic synapse. We investigated the AMPA receptor composition and shuttling in adult Fmr1 KO and WT mice using a variety of complementary experimental strategies such as surface protein crosslinking, immunostaining of surface receptors and electrophysiology. We discovered that the activity-dependent synaptic delivery of AMPARs is impaired in adult Fmr1 KO mice. Furthermore, we show that Fmr1 KO synaptic AMPARs contain more GluA2 subunits what can be interpreted as a switch in synaptic AMPAR subtype toward an increased number of Ca 2+-impermeable receptors in adult Fmr1 KO synapses.